3β-Hydroxy-Δ5-steroidal congeners from a column fraction of Dendronephthya puetteri attenuate LPS-induced inflammatory responses in RAW 264.7 macrophages and zebrafish embryo model. Issue 33 (22nd May 2018) - Fernando, I. P. Shanura; Lee, Won Woo; Jayawardena, Thilina U.; Kang, Min-Cheol; Ann, Yong-Seok; Ko, Chang-ik; Park, Young Jin; Jeon, You-Jin
Abstract : Bioactive compounds from marine organisms and their action mechanisms have provided new insights into medicinal and natural product research. Abstract : Bioactive compounds from marine organisms and their action mechanisms have provided new insights into medicinal and natural product research. Here, we report the identification of 3β-hydroxy-Δ5-steroidal congeners from a purified column fraction (DPCMH24) of the soft coral Dendronephthya puetteri harvested from Jeju, South Korea. DPCMH24 exerted strong anti-inflammatory effects through a dose-dependent decrease in the levels of nitric oxide (NO) in LPS-induced RAW 264.7 macrophages (IC50 value = 6.54 ± 0.38 μg mL −1 ). Further, DPCMH24 attenuated the levels of PGE2 and the pro-inflammatory cytokines, TNF-α, IL-1β, and IL-6. The above effects were mediated via the inhibition of nuclear factor κB activation and mitogen-activated protein kinase pathways. In vivo evaluation indicated that DPCMH24 reduced NO, iNOS, COX-2, ROS production and cell death in LPS-induced zebrafish embryos, confirming its anti-inflammatory potential. The constituent compounds were identified by GC-MS/MS analysis. These findings suggest that the steroidal congeners from D. puetteri may offer ample therapeutic potential against LPS-induced inflammation.